Updated Global Warming Potentials and Radiative Efficiencies of Halocarbons and Other Weak Atmospheric Absorbers. (7th September 2020) - Hodnebrog, Ø.; Aamaas, B.; Fuglestvedt, J. S.; Marston, G.; Myhre, G.; Nielsen, C. J.; Sandstad, M.; Shine, K. P.; Wallington, T. J.
Abstract: Human activity has led to increased atmospheric concentrations of many gases, including halocarbons, and may lead to emissions of many more gases. Many of these gases are, on a per molecule basis, powerful greenhouse gases, although at present‐day concentrations their climate effect is in the so‐called weak limit (i.e., their effect scales linearly with concentration). We published a comprehensive review of the radiative efficiencies (RE) and global warming potentials (GWP) for around 200 such compounds in 2013 (Hodnebrog et al., 2013, https://doi.org/10.1002/rog.20013 ). Here we present updated RE and GWP values for compounds where experimental infrared absorption spectra are available. Updated numbers are based on a revised "Pinnock curve", which gives RE as a function of wave number, and now also accounts for stratospheric temperature adjustment (Shine & Myhre, 2020, https://doi.org/10.1029/2019MS001951 ). Further updates include the implementation of around 500 absorption spectra additional to those in the 2013 review and new atmospheric lifetimes from the literature (mainly from WMO (2019)). In total, values for 60 of the compounds previously assessed are based on additional absorption spectra, and 42 compounds have REs which differ by >10% from our previous assessment. New RE calculations are presented for more than 400 compounds in addition to the previously assessed compounds, and GWP calculations are presented for a total of around 250 compounds. Present‐day radiative forcing due to halocarbons and other weak absorbers is 0.38 [0.33–0.43] W m −2, compared to 0.36 [0.32–0.40] W m −2 in IPCC AR5 (Myhre et al., 2013, https://doi.org/10.1017/CBO9781107415324.018 ), which is about 18% of the current CO2 forcing. Plain Language Summary: Human activity has led to increased atmospheric concentrations of many gases, including halocarbons (used, e.g., in refrigeration and air conditioning), and may lead to emissions of many other gases. While some halocarbons, such as chlorofluorocarbons (CFCs), are known to deplete stratospheric ozone, they are also powerful greenhouse gases contributing to radiative forcing (the net change in the energy balance of the Earth system) and hence climate change. We find that the present‐day contribution from halocarbons and related compounds to radiative forcing is about 18% of the forcing due to increased concentrations of CO2 . By using established methods and available laboratory measurements of absorption of infrared radiation for each gas, we quantify the radiative efficiency (i.e., a compound's strength as a greenhouse gas) for a total of around 600 compounds. For around 250 compounds we provide so‐called global warming potentials (GWP), which are used to compare the climate impact of emissions of different gases and are commonly used to inform policy decisions. Results presented here can be used to derive values for emission metrics other than GWP. The present work is the most comprehensive review of the radiative efficiency and GWP of halocarbons and other weak absorbers performed to date. Key Points: Radiative efficiencies are reassessed for more than 600 compounds and global warming potentials calculated for around 250 of these Forty‐two compounds have >10% different radiative efficiency compared to a comprehensive review in 2013 Present‐day radiative forcing due to halocarbons and other weak absorbers is 0.38 [0.33–0.43] W m −2, which is 18% of the CO2 forcing